Pengaruh pertumbuhan perusahaan, struktur kepemilikan, dan pajak terhadap pembayaran dividen - Cahyani, Della Rizky; Lisiantara, G. Anggana (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
This study aims to examine more deeply what factors can affect dividend payments by companies. Quantitative techniques are applied in research design. This study takes secondary data contained on the official website of the Indonesia Stock Exchange using a purposive selection strategy. In total, 203 manufacturing companies selling on the Indonesia Stock Exchange were used as part of this study population. Methods of data analysis using multiple regression analysis. According to the findings of this research, the dividend policy of a firm is unaffected by the expansion of the company or its ownership structure; nevertheless, dividend policy is affected by taxation.